Human papillomavirus type 11 E2 proteins repress the homologous E6 promoter by interfering with the binding of host transcription factors to adjacent elements. - Dong, G (1994)
The E6 promoter of human papillomaviruses (HPVs) trophic for epithelia for the lower genital tract and the upper respiratory tract is regulated in vitro by homologous and heterologous papillomaviral E2 proteins that bind to a consensus responsive sequence (E2-RS) ACCN6GGT. When HPV type 11 (HPV-11) expression is examined in epithelial cell lines, the HPV-11 E2-C protein, which lacks the amino-terminal transactivating domain of the full-length E2 protein, invariably represses the homologous viral E6 promoter. In contrast, when the novel constitutive enhancer (CE) CE II is deleted, not only is the basal promoter activity much reduced, it is further repressed by the intact HPV-11 E2 protein (M. T. Chin, T. R. Broker, and L. T. Chow, J. Virol. 63:2967-2976, 1989). Here, we demonstrated that, when expressed from a stronger surrogate promoter, the HPV-11 E2 protein represses the E6 promoter effectively, regardless of CE II. By performing systematic mutational analyses of the four highly conserved copies of the HPV-11 E2-RS and of the adjacent enhancer-promoter elements, we show that the furthest upstream, promoter-distal E2-RS copy 1 plays no apparent role in E6 promoter regulation. Repression by the homologous HPV-11 E2 proteins is mediated through each of the three promoter-proximal copies of the E2-RS, but the presence of CE II abrogates the full-length E2 protein repression exerted at E2-RS copy 2. Repression is alleviated when the two (for E2) or three (for E2-C) promoter-proximal copies of E2-RS are mutated. We specifically demonstrate that repression exerted at E2-RS 3 is due to preclusion of binding of the host transcription factor Sp1 or Sp1-like proteins to a nonconsensus sequence AGGAGG located 1 bp upstream of the tandem E2 protein binding sites 3 and 4. A 3-bp insertion between the adjacent Sp1 and E2-RS 3 sites permits both Sp1 and E2 proteins to bind, with a concomitant relief of E2-RS 3-mediated repression. Similar mutational analyses show that proteins that bind to the GT-1 motif near the upstream E2-RS 2 help abrogate repression by the E2 protein in the presence of CE II. The implications of these results with respect to the viral infectious cycle and during viral oncogenesis are discussed.